Impact of the species ratio in polyculture on growth and weight of bivalve mollusks in the Tauiskaya Guba Bay, Okhotsk Sea - V. S. Zharnikov (Известия ТИНРО)
Linear growth and weight of bivalve mollusks cultivated in polyculture are considered. Cages with three mollusk species, as blue mussel, long-necked clam (mya), and macoma, were hanged at the depth of 1.0–1.5 m in the Tauiskaya Guba Bay, Okhotsk Sea. Several sets of these species with ratio mussel : mya : macoma 30 : 35 : 35, 50 : 25 : 25 and 70 : 15 : 15 were tested in the period from June 15 to October 26. The species ratio of 30 : 35 : 35 and 50 : 25 : 25 provided the highest linear increments for mussels (7.4 ± 0.3 and 7.1 ± 0.5 mm, respectively) and the highest weight increments for mya (7.8–8.2 g). The species ratio of 70 : 15 : 15 was the most favorable for weight growth of macoma (weight increments 1.6 ± 0.1 g). Mussels were distinguished by the largest elimination among all species in the polyculture — 7.5–8.8 %, whereas losses of macoma were the lowest — 1.9–2.1 %. The polyculture is considered as a prospective approach for bivalve mollusks cultivation in the northern Okhotsk Sea.